BEYOND COMPLIANCE: EXPLORATION OF PSYCHOSOCIAL AND ORGANIZATIONAL FACTORS THAT AFFECT PERSONAL PROTECTIVE EQUIPMENT COMPLIANCE AND ITS IMPLICATIONS FOR THE INCIDENCE OF HAIS IN EMERGENCY DEPARTMENT HEALTH WORKERS AT RSIA ARTHA MAHINRUS - Jennifer Tiosanna; Ermi Girsang; Sri Lestari Ramadhani Nasution (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aimed to analyze psychosocial and organizational factors influencing Personal Protective Equipment (PPE) compliance and their implications for Healthcare-Associated Infections (HAIs) among emergency department healthcare workers at RSIA Artha Mahinrus. This study used a mixed-methods approach with a sequential explanatory design, in which quantitative data were collected first, followed by qualitative data to deepen the findings. The quantitative sample comprised 16 healthcare workers (4 doctors, 4 nurses, and 8 midwives) using a total sampling approach. Data were analyzed using univariate, bivariate (Fisher's Exact Test), and multivariate (multiple linear regression) analyses. Qualitative data were obtained through in-depth interviews. The results showed that psychosocial factors (p = 0.030) and organizational factors (p = 0.012) significantly influenced PPE compliance, with organizational factors as the dominant predictor. The findings also revealed the phenomenon of clinical discretion, in which emergencies and time pressure led to intentional noncompliance with PPE protocols. In addition, a paradox was identified: high organizational involvement was associated with noncompliance due to safety complacency and perceived bureaucratic burden. These findings indicate that PPE compliance is not merely adherence to standard procedures but reflects a complex interaction between individual and organizational factors in maintaining patient and worker safety.